Carpobrotus edulis (L.) N.E. Br. (Aizoaceae) y su presencia en la flora de Chile - Sotes, Gastón J.; Cavieres, Lohengrin A.; Rodríguez, Roberto (Gayana Botánica, 2015)
The genus Carpobrotus was represented on the Chilean flora only by native species C. chilensis. However, we found that the species native of South Africa C. edulis is naturalized in coastal areas. We report it for first time as an alien species for the Chilean territory.